Determination of Mammalian Target of Rapamycin Hyperactivation as Prognostic Factor in Well-Differentiated Neuroendocrine Tumors. (29th October 2017) - Lamberti, G.; Ceccarelli, C.; Brighi, N.; Maggio, I.; Santini, D.; Mosconi, C.; Ricci, C.; Biasco, G.; Campana, D.
Abstract : Purpose . To evaluate the role of the activation of mTOR (phosphorylated mTOR, p-mTOR) and the expression SSTR2A and IGF-1R as prognostic factor in well-differentiated neuroendocrine tumors. Methods . A retrospective study was conducted on data from patients with diagnosis of neuroendocrine tumor originated from pancreas (pNET) or gastrointestinal tract (stomach, appendix, and ileus; GI-NET) made between January 2003 and December 2004 and followed up at our institution. Archival material should be available for revision according to WHO 2010 neuroendocrine tumor classification and for p-mTOR, SSTR2A, and IGF-1R immunostaining, calculating a quantitative score (QS). We evaluated clinical, pathological, and immunohistochemistry features for association with the presence of advanced disease at diagnosis and disease relapse in patients who have undergone radical surgery. Results . Archival material from 64 patients was analyzed (37 pNETs and 27 GI-NETs). In these patients, G2 grading, low SSTR2A QS, and high p-mTOR QS were associated with advanced disease at diagnosis at multivariate analysis. Risk of recurrence in 49 patients with R0-resected tumors was higher for G2 grading, stage IIIB-IV, low IGF-1R QS, and high p-mTOR QS at univariate analysis. Conclusions . With the limits of retrospective data, activation of m-TOR is correlated with advanced disease at diagnosis and with shorter disease-free survival after R0 resection. Validation through prospective studies is needed.